THE COMPARISON OF TECHNICAL EFFICIENCY ON CATTLE BREEDING BUSINESS BETWEEN SHARE-BEEF CATTLE MODEL AND FARMER-OWN BEEF CATTLE MODEL AT MUARO JAMBI REGENCY, JAMBI PROVINCE - Bagus Pramusintho; Slamet Hartono; Dwidjono Hadi Darwanto; Any Suryantini (Buletin Peternakan, 2017)
The lack of capital for investment and limited access for small beef cattle farming to obtain credit from financial institution have contributed to the occurrence of share-beef cattle in rural areas. Through share-beef cattle pattern, the farmers (tenant) can rent livestock from other parties (individual nor government) within a share-beef cattle contract agreement. The purposes of this study were to determine the technical efficiency and the factors which influence the inefficiency from 108 small beef cattlebreeding, which consists of 59 farming operated by owner and 49 operated by tenant.  The unit samples were selected by snowball sampling method and analysed by Stochastic Frontier Production. Our study showed that the average technical efficiency of beef cattle breeding operated by owner was at 0.73, otherwise operated by tenant was at 0.790. The inefficiency of beef cattle breeding operated by owner has negatively corresponded to the number of cows, the farmer age, the age of cow and the application of artificial insemination (IA), but positively corresponded to allocation of family labour and level of farmer education. The inefficiency of beef cattle breeding operated by a tenant has negatively corresponded to the application of artificial insemination (AI). Specific conclusion of the study was the technical efficiency level of small beef cattle breeding was not only affected by the ownership of beef cattle but also by the pattern of share-beef cattle.  The share-beef cattle based on share income(50:50) may improve the value of technical efficiency compared to share-beef cattle based on share in-kind (share-beef cattle revolving cow or share-beef cattle revolving calf).